Coating film
The glass-based coating film with dispersed silver, copper, and zinc ions addresses the limitations of existing technologies by providing long-lasting and effective antibacterial, antiviral, and anti-mold protection for various substrates.
Patent Information
- Application Number
- JP2024148202
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-02
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Existing coating technologies for glass substrates face challenges in introducing large amounts of silver ions, which limits their antibacterial and antiviral effectiveness and durability.
A glass-based coating film is developed, incorporating dispersed glass particles made of silver ions, copper ions, and zinc ions, which are electrically conductive and allow for a high concentration of these ions within the coating film.
The coating film achieves excellent antibacterial, antiviral, anti-mold, and deodorizing functions, effectively killing bacteria, viruses, and mold, while maintaining these properties for a long period and applying them to various substrates.
Smart Images

Figure 2025062566000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating film. [Background technology]
[0002] A coated glass is disclosed, which is formed of a glass substrate and a coating formed on the surface of the glass substrate, the coating having a silicon oxide matrix, containing silver ions and at least one alkali metal ion selected from sodium, potassium and lithium, and which has a yellowness index YI calculated according to JIS-K7373 (2006) before and after a humidity resistance test in which the glass is held in a high-temperature, high-humidity chamber at 85°C and 85% RH for 1000 hours, and has an antibacterial activity value of 2.0 or more one hour after the start of an antibacterial test performed on the surface of the coating in a dark place at 25°C according to JIS Z 2801 (2010) (see Patent Document 1). This coated glass is used as glass windows for buildings and automobiles. The inclusion of silver in the coated glass gives it antibacterial and antiviral properties, and also helps prevent the yellowing caused by silver. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-33109 A Summary of the Invention [Problem to be solved by the invention]
[0004] The coated glass disclosed in Patent Document 1 has a coating with a silicon oxide matrix, so it is difficult to introduce a large amount of silver ions into the coating, and since the coating does not contain a large amount of silver ions, the antibacterial and antiviral function of the coating is small, it is difficult to reliably kill germs and various viruses, and the antibacterial and antiviral function of the coating cannot be maintained for a long period of time. In addition, this coated glass has a coating with a silicon oxide matrix, and is made by forming a coating containing silver ions and at least one alkali metal ion selected from sodium, potassium, and lithium on the surface of a glass substrate, so it is not intended to form a coating on a substrate other than a glass substrate, and it is not possible to impart antibacterial or antiviral properties to substrates other than a glass substrate.
[0005] The object of the present invention is to provide a coating film capable of introducing a large amount of silver ions, copper ions, and zinc ions and containing a large amount of silver ions, copper ions, and zinc ions. Another object of the present invention is to provide a coating film having excellent antibacterial, antiviral, antifungal, and deodorizing functions, capable of reliably killing germs, various viruses, and various mold fungi, and capable of reliably removing unpleasant odors. Another object of the present invention is to provide a coating film capable of imparting excellent antibacterial, antiviral, antifungal, and deodorizing functions to all coating objects, regardless of the object to be coated, and capable of sustaining the antibacterial, antiviral, antifungal, and deodorizing functions for a long period of time. [Means for solving the problem]
[0006] The premise of the present invention for solving the above problems is a coating film in which glass particles are dispersed and mixed.
[0007] The feature of the present invention based on the above premise is that the coating film is a glass-based coating film based on silicon oxide (SiO2), and the glass particles are silver ions (Ag + ), copper ions (Cu 2+ ), zinc ion (Zn 2+) is a conductive glass containing at least one of the above.
[0008] In one embodiment of the present invention, the glass particles dispersed in the coating film are ionized with silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ ) and silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ ) and at least one of them.
[0009] In another embodiment of the present invention, glass particles dispersed in the coating film are ionized with silver ions (Ag + ), conductive glass containing only copper ions (Cu 2+ Conductive glass containing only ions (Zn 2+ ) is a conductive glass containing only
[0010] In another embodiment of the present invention, glass particles dispersed in the coating film are ionized with silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ ) and conductive glass containing at least silver ions (Ag + ) is a conductive glass containing only
[0011] In one embodiment of the present invention, the glass particles include a glass based on at least one of vanadium oxide (V2O5), tungsten oxide (WO3), molybdenum oxide (MoO3), and phosphorus oxide (P2O5).
[0012] In another embodiment of the present invention, the glass particles are + ) is a vanadium oxide (V2O5)-phosphorus oxide (P2O5) glass.
[0013] In another embodiment of the present invention, the glass particles further include barium oxide (BaO).
[0014] In another example of the present invention, the content of glass particles dispersed and mixed in the coating film is 0.1% by volume or more and 30% by volume or less.
[0015] In another example of the present invention, the content of glass particles dispersed and mixed in the coating film is 0.2 volume % or more and 10 volume % or less.
[0016] In another embodiment of the present invention, the average particle diameter D 50 However, it is less than 5 μm.
[0017] In another embodiment of the present invention, the average particle diameter D 50 However, it is less than 3 μm.
[0018] As another example of the present invention, in the case of a coating film, after a coating liquid for forming the coating film is coated on the surface of a predetermined substrate, metal ions of glass particles mixed in the coating liquid diffuse into the inside of the coating film.
[0019] As another example of the present invention, in the coating film, metal ions of glass particles mixed in a coating liquid diffuse inside the coating film and move to the surface of the coating film.
[0020] In another example of the present invention, the original coating liquid (starting material for the coating film) is a siloxane-based solution or a silica sol-based solution, and glass particles are mixed into the siloxane-based solution or the silica sol-based solution.
[0021] In another example of the present invention, the coating film is a glass-based organic / inorganic hybrid coating film. Effect of the Invention
[0022] According to the coating film of the present invention, the coating film is a glass-based coating film based on silicon oxide (SiO2), and the glass particles are silver ions (Ag +), copper ions (Cu 2+ ), zinc ion (Zn 2+ ), and since the glass particles containing metal ions have electronic conductivity, a large amount of silver ions, copper ions, and zinc ions can be introduced, and the coating film can contain a large amount of silver ions, copper ions, and zinc ions. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various germs, various viruses, and various mold bacteria and can reliably remove unpleasant odors. The coating film is not limited to the object to be coated, and can impart excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions to all substrates (objects to be coated), and by containing a large amount of silver ions, copper ions, and zinc ions, the antibacterial and antiviral functions, antifungal functions, and deodorizing functions can be maintained for a long period of time.
[0023] The glass particles are silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ ) and silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ The coating film is made of conductive glass containing at least one of these metal ions, and the glass particles containing these metal ions have electronic conductivity, so a large amount of silver ions, copper ions, and zinc ions can be introduced, and the coating film can contain a large amount of silver ions, copper ions, and zinc ions. + ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ) of silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+) and / or other suitable compounds, the product has excellent antibacterial, antiviral, antifungal and deodorizing properties, can reliably kill germs, various viruses and various mold spores, and can reliably eliminate unpleasant odors while maintaining its antibacterial, antiviral, antifungal and deodorizing properties for a long period of time.
[0024] The glass particles are silver ions (Ag + ), conductive glass containing only copper ions (Cu 2+ ), a conductive glass containing only zinc ions (Zn 2+ The coating film is made of conductive glass containing only silver, copper, and zinc ions diffuse from the glass particles into the coating film at roughly the same time, giving the coating film excellent antibacterial, antiviral, antifungal, and deodorizing functions, and can reliably kill various germs, viruses, and various mold spores, and can reliably eliminate unpleasant odors.
[0025] The glass particles are silver ions (Ag + ) and copper ions (Cu 2+ ) and zinc ions (Zn 2+ ) and conductive glass containing at least silver ions (Ag + The coating film is made of conductive glass containing only silver ions, and at least silver ions are diffused from the glass particles into the coating film, which gives the coating film excellent antibacterial, antiviral, antifungal and deodorizing functions, and can reliably kill germs, various viruses and various mold spores, and remove unpleasant odors.
[0026] The coating film, in which glass particles contain glass based on at least one of vanadium oxide (V2O5), tungsten oxide (WO3), and molybdenum oxide (MoO3), and phosphorus oxide (P2O5), has high electronic conductivity due to the inclusion of glass based on at least one of vanadium oxide (V2O5), tungsten oxide (WO3), and molybdenum oxide (MoO3), and phosphorus oxide (P2O5). This allows the glass particles to have high electronic conductivity, so that a large amount of silver ions, copper ions, and zinc ions can be introduced into the coating film, and the coating film can contain a large amount of silver ions, copper ions, and zinc ions. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various bacteria, various viruses, and various mold bacteria, and can reliably remove unpleasant odors. The coating film is not limited to the object it covers, and can impart excellent antibacterial, antiviral, antifungal and deodorizing functions to all base materials (objects to be coated). Because it contains a large amount of silver, copper and zinc ions, its antibacterial, antiviral, antifungal and deodorizing functions can be sustained for a long period of time.
[0027] The glass particles are silver ions (Ag +The coating film, which is a vanadium oxide (V2O5)-phosphorus oxide (P2O5)-based glass containing silver ions, uses vanadium oxide-phosphorus oxide-based glass containing silver ions as glass particles, and since the glass particles have high electronic conductivity, a large amount of silver ions, copper ions, and zinc ions can be introduced into the coating film, and the coating film can contain a large amount of silver ions, copper ions, and zinc ions. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various germs, various viruses, and various mold bacteria and can reliably remove unpleasant odors. The coating film is not limited to the object to be coated, and can impart excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions to all substrates (objects to be coated), and by containing a large amount of silver ions, copper ions, and zinc ions, the antibacterial and antiviral functions, antifungal functions, and deodorizing functions can be sustained for a long period of time.
[0028] The glass particles are silver ions (Ag + The coating film, which is a vanadium oxide (V2O5)-phosphorus oxide (P2O5)-barium oxide (BaO)-based glass containing silver ions, uses vanadium oxide-phosphorus oxide-based glass containing silver ions as glass particles, and since the glass particles have high electronic conductivity, a large amount of silver ions, copper ions, and zinc ions can be introduced into the coating film, and the coating film can contain a large amount of silver ions, copper ions, and zinc ions. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various germs, various viruses, and various mold bacteria and can reliably remove unpleasant odors. The coating film is not limited to the object to be coated, and can impart excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions to all substrates (objects to be coated), and by containing a large amount of silver ions, copper ions, and zinc ions, the antibacterial and antiviral functions, antifungal functions, and deodorizing functions can be maintained for a long period of time.
[0029] A coating film having a glass particle content of 0.1% by volume or more and 30% by volume or less has excellent antibacterial, antiviral, antifungal and deodorizing functions, and can reliably kill germs, various viruses and various molds, and can reliably remove unpleasant odors. The coating film is not limited to the object to be covered, and can impart excellent antibacterial, antiviral, antifungal and deodorizing functions to all substrates (objects to be covered), and by containing glass particles with a content in the above range, the antibacterial, antiviral, antifungal and deodorizing functions can be sustained for a long period of time.
[0030] A coating film having a glass particle content of 0.2% by volume or more and 10% by volume or less has excellent antibacterial, antiviral, antifungal and deodorizing functions, and can reliably kill germs, various viruses and various molds, and can reliably remove unpleasant odors. The coating film is not limited to the object to be covered, and can impart excellent antibacterial, antiviral, antifungal and deodorizing functions to all substrates (objects to be covered), and by containing glass particles with a content in the above range, the antibacterial, antiviral, antifungal and deodorizing functions can be sustained for a long period of time.
[0031] Average glass particle size D 50The coating film having an average particle size of 5 μm or less can introduce a large amount of silver ions, copper ions, and zinc ions into the coating film by using glass particles having the above average particle size, and can contain a large amount of silver ions, copper ions, and zinc ions in the coating film. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various germs, various viruses, and various mold bacteria and can reliably remove unpleasant odors. The coating film is not limited to the object to be covered, and can impart excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions to all substrates (objects to be covered), and can maintain its antibacterial and antiviral functions, antifungal functions, and deodorizing functions for a long period of time by containing a large amount of silver ions, copper ions, and zinc ions.
[0032] Average glass particle size D 50 The coating film having an average particle size of 3 μm or less can introduce a large amount of silver ions, copper ions, and zinc ions into the coating film by using glass particles having the above average particle size, and can contain a large amount of silver ions, copper ions, and zinc ions in the coating film. Since the coating film contains a large amount of silver ions, copper ions, and zinc ions, it has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various germs, various viruses, and various mold bacteria and can reliably remove unpleasant odors. The coating film is not limited to the object to be covered, and can impart excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions to all substrates (objects to be covered), and can maintain its antibacterial and antiviral functions, antifungal functions, and deodorizing functions for a long period of time by containing a large amount of silver ions, copper ions, and zinc ions.
[0033] After the coating liquid that forms the coating film is applied to the surface of a specified substrate, the metal ions of the glass particles mixed in the coating liquid diffuse into the coating film, and the metal ions diffuse into the coating film exert high antibacterial, antiviral, antifungal and deodorizing functions, so the coating film has excellent antibacterial, antiviral, antifungal and deodorizing functions, and can reliably kill germs, various viruses and various mold fungi, and can reliably eliminate unpleasant odors.
[0034] The metal ions of the glass particles mixed in the coating liquid diffuse inside the coating film and migrate to the surface of the coating film. The metal ions that diffuse inside the coating film and migrate to the surface of the coating film exhibit high antibacterial, antiviral, antifungal and deodorizing functions, so the coating film has excellent antibacterial, antiviral, antifungal and deodorizing functions and can reliably kill germs, various viruses and various mold fungi and can reliably eliminate unpleasant odors.
[0035] The coating liquid stock solution (starting material for the coating film) is a siloxane-based solution or a silica sol-based solution, and the coating film in which glass particles are mixed into the siloxane-based solution or the silica sol-based solution uses a siloxane-based solution or a silica sol-based solution with a porous molecular structure as the coating liquid stock solution (starting material for the coating film), so that a large amount of silver ions, copper ions, and zinc ions can be mixed into the siloxane-based solution or the silica sol-based solution, and a coating film made from the siloxane-based solution or the silica sol-based solution can contain a large amount of silver ions, copper ions, and zinc ions, and a large amount of metal ions can be diffused into the inside of the coating film. Since a large amount of silver ions, copper ions, and zinc ions are diffused into the coating film, the coating film has excellent antibacterial and antiviral functions, antifungal functions, and deodorizing functions, and can reliably kill various bacteria, various viruses, and various mold bacteria, and can reliably remove unpleasant odors.
[0036] The coating film, which is a glass-based organic / inorganic hybrid coating film, has excellent antibacterial, antiviral, antifungal and deodorizing functions because the glass-based organic / inorganic hybrid coating film contains a large amount of silver ions, copper ions, and zinc ions, and can reliably kill various germs, various viruses, and various mold bacteria and reliably remove unpleasant odors. The coating film is not limited to the object to be covered with the glass-based organic / inorganic hybrid coating film, and can impart excellent antibacterial, antiviral, antifungal and deodorizing functions to all substrates (subjects to be covered), and can maintain its antibacterial, antiviral, antifungal and deodorizing functions for a long period of time because it contains a large amount of silver ions, copper ions, and zinc ions. The coating film, which is a glass-based organic / inorganic hybrid coating film, has excellent strength and scratch resistance, and can prevent scratches on the substrate on which the glass-based organic / inorganic hybrid coating film is formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The coating film according to the present invention will be described in detail with reference to the accompanying drawings. Fig. 1 is an enlarged cross-sectional image of an organic / inorganic hybrid coating film 10 formed on a surface 12 of a substrate 11, and Fig. 2 is a cross-sectional view for explaining in a time series manner the mechanism by which an organic / inorganic hybrid coating film 10 is formed from a coating liquid 13 on the surface 12 (front and back) of a substrate 11 to which the coating liquid 13 has been applied. Fig. 3 is a cross-sectional view showing a schematic example of a state immediately after the coating liquid 13 has been applied to the surface 12 (front and back) of the substrate 11, and Fig. 4 is a cross-sectional view showing a schematic example of a state after the organic / inorganic hybrid coating film 10 has been formed on the surface 12 of the substrate 11.
[0038] FIG. 5 is a cross-sectional view showing a schematic example of another example of a state immediately after coating (applying) the coating liquid 13 on the surface 12 (front and back) of the substrate 11, and FIG. 6 is a cross-sectional view showing a schematic example of another example of a state after the organic / inorganic hybrid coating film 10 is formed on the surface 12 of the substrate 11. FIG. 7 is an image showing an example of the structure of the organic / inorganic hybrid coating film 10, and FIG. 8 is an image showing an example of the state of metal ions in the organic / inorganic hybrid coating film 10. In FIGS. 1, 3, 4, 5, 6, and 8, glass particles 14, silver ions 15a (Ag + ), copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) is illustrated as a visible image of metal ions 15, however, in reality metal ions 15 cannot be seen with the naked eye.
[0039] The organic / inorganic hybrid coating film 10 (coating film) is formed on a surface 12 (front surface, back surface) (contact surface) of a substrate 11. The organic / inorganic hybrid coating film 10 is produced by coating (applying) a coating liquid 13 (organic and inorganic hybrid polymer) on the surface 12 of the substrate 11 to be coated. The substrate 11 to be coated with the coating liquid 13 (subject to which the organic / inorganic hybrid coating film 10 (coating film)) may be plastic (plastic molded products and molded products having plastic in the outermost layer), glass (glass molded products), metal (metal molded products), rubber (rubber molded products), leather (leather molded products), wood (wood molded products), paper (paper molded products, woven and knitted fabrics using fibers (woven and knitted fabric molded products), and nonwoven fabrics (nonwoven fabric molded products), but the substrate 11 is not particularly limited.
[0040] Examples of plastics include known thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyamide (nylon), vinyl chloride resin, acrylic resin, silicone resin, fluororesin, polyimide resin, polysulfone resin, etc., and thermosetting resins such as epoxy resin, melamine resin, phenol resin, unsaturated polyester resin, etc. Examples of metals include iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, alloys, etc.
[0041] Examples of molded articles include medical clothing (masks, lab coats, protective clothing, gloves, etc.), medical bedding (futons, pillowcases, curtains, patient amenities, etc.), medical instruments (scissors, scalpels, other equipment, etc.), hospital facilities (handrails, doorknobs, walls, floors, elevators, escalators, etc.), means of transportation (trains, buses, airplanes, ships, vehicles, etc.), clothing (underwear, T-shirts, socks, sportswear, diapers, etc.), pet supplies (pet toilets, pet cages, etc.), sanitary products (kitchen supplies, toilet supplies, bath supplies, washbasins, etc.), food supplies (food trays, kitchen supplies, tableware, etc.), and in addition, all molded articles that are subject to antibacterial, antiviral, anti-fungal, and deodorizing properties are included.
[0042] The starting material (coating stock solution) of the coating liquid 13 (organic and inorganic hybrid polymer) is made from a liquid organosilicon material solution (silicon material solution) consisting of at least one of siloxane (siloxane-based solution), polysilazane (inorganic polysilazane, organic polysilazane), and silica sol (silica sol-based solution), an alkyl silicate condensate, an inert organic solvent, and glass particles 14 described below. As an example of the siloxane, an organopolysiloxane in which silicon atoms (Si) having organic groups are linked by siloxane bonds (≡Si-O-Si≡) is used. The number average molecular weight of the organopolysiloxane is in the range of 3000 to 150000 g / mol.
[0043] The coating liquid 13 (organic and inorganic hybrid polymer) may be made of either siloxane or polysilazane, or may be a mixture of both. An organosilicon material, an alkylsilicate condensate, and an inert organic solvent are mixed and stirred at a predetermined ratio, and glass particles 14 are mixed into the mixture to produce the coating liquid 13. In the coating liquid 13, an organosilicon material made of at least one of siloxane and polysilazane, and an alkylsilicate condensate are diluted with an inert organic solvent.
[0044] Inorganic polysilazanes include Si-N perhydropolysilazanes (perhydropolysilazanes). As polysilazanes, Si-CN organopolysilazanes, Si-C polycarbosilanes, and SiC-O, Si-BCN, and Si-Ti-N polysilazanes can also be used.
[0045] As the organic polysilazane, modified polysilazanes such as methylpolysilazane, dimethylpolysilazane, phenylpolysilazane, vinylpolysilazane, etc. can also be used. Also usable is a crosslinked polysilazane that is chemically crosslinked with a compound such as a hydrocarbon compound having a reactive group such as a hydroxyl group, a vinyl group, an amino group, or a silyl group that chemically reacts with polysilazane to form a crosslinked structure, a cyclic saturated hydrocarbon compound, a cyclic unsaturated hydrocarbon compound, a saturated heterocyclic compound, an unsaturated heterocyclic compound, or a silicone compound.
[0046] In addition, polyborosilazane, inorganic silazane high polymers or modified polysilazanes, copolymerized silazanes, low-temperature ceramicized polysilazanes obtained by adding or incorporating a catalytic compound to polysilazane to promote ceramicization, silicon alkoxide-added polysilazanes, glycidol-added polysilazanes, acetylacetonato complex-added polysilazanes, metal carboxylate-added polysilazanes, and polysilazane compositions obtained by adding amines and / or acids to the above-mentioned various polysilazanes or modified products can also be used.
[0047] The polysilazane may be one type of single polysilazane, a mixture of two or more types of polysilazanes selected from various polysilazanes, or a polysilazane copolymer consisting of two or more types of polysilazane structures, and contains at least one hydrogen atom directly bonded to a silicon atom in one molecule. The polysilazane forming the coating liquid 13 has a weight average molecular weight in the range of 100 to 100,000,000, preferably 1,000 to 1,000,000, and more preferably 2,000 to 500,000, from the viewpoints of solubility in a solvent and workability during application. If the weight average molecular weight is 100 or more, the volatility is low, and the polysilazane itself volatilizes during the volatilization of the solvent and the curing process, which may deteriorate the film quality of the coating film.
[0048] The inorganic polysilazane is represented by the general formula (Chemical Formula 1).
[0049] [ka] Examples of inorganic polysilazanes include perhydropolysilazane that includes a linear structure having structural units, has a molecular weight of 690 to 2,000, has 3 to 10 SiH3 groups in one molecule, and has element ratios by weight of Si: 59 to 61, N: 31 to 34, and H: 6.5 to 7.5 as determined by chemical analysis, and has a polystyrene-equivalent average molecular weight in the range of 3,000 to 20,000.
[0050] Perhydropolysilazane contains chain and cyclic portions in its molecule and is represented by the following chemical formula (Chemical Formula 2).
[0051] [ka] An example of the structure of perhydropolysilazane is represented by the following chemical formula (Chemical Formula 3).
[0052] [ka] Another example of the perhydropolysilazane compound group is represented by the following general formula (Chemical Formula 4), which has a Si-N bond and a functional group (R 1 ~R 3 ) and is a polymer formed from -(SiR1R2-NR3)- units, and at least one of the functional groups R1 and R2 that are directly bonded to Si is an organic polymer formed from an organic functional group such as an alkyl group having carbon (C).
[0053] [ka] Perhydropolysilazane is a functional group (R 1 ~R 3 The content of methyl group (CH3), which is one of the functional groups, is 50% or more. Perhydropolysilazane may be not only a polymer formed from one type of -(SiR1R2-NR3)- unit, but also a polymer formed from multiple types of -(SiR1R2-NR3)- units having different compositions of functional groups (R1 to R3). Furthermore, perhydropolysilazane may be a polymer having a chain, cyclic or crosslinked structure, or may be a polymer having a combination of these structures. R 1 , R 2 , R 3 represents a hydrogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an aryl group, or a group other than these groups in which the group directly bonded to silicon is carbon, an alkylsilyl group, an alkylamino group, or an alkoxy group. 1 , R 2 , R 3 At least one of is a hydrogen atom.
[0054] As an example, perhydropolysilazane (A) is a -(SiH(CH3)-NH)- unit, -(Si(CH3)2-NH)- unit, -(SiR 1 It is a polymer containing (CH3)-NR3)- units. 1 (CH3)-NR 3The functional group R1 in the )-unit is H or CH3, and the functional group R3 directly bonded to N is an organic functional group that promotes the reaction. By including perhydropolysilazane (A) in the coating liquid 13, the reaction after the coating liquid 13 is coated on the surface 12 of the article 11 is promoted, and the organic / inorganic hybrid coating film 13 can be formed on the surface 12 of the article 11 at an early stage.
[0055] [ka] Another example of perhydropolysilazane (B) is a -(SiH(CH3)-NH)- unit represented by the following general formula (Chemical Formula 6), -(SiR 1 (CH3)-NH)- units, and -(SiR 1 Functional group R of the (CH3)-NH)- unit 1 is an organic functional group that realizes high heat resistance. By including perhydropolysilazane (B) in the coating liquid 13, the heat resistance of the organic / inorganic hybrid coating film 13 that covers the surface 12 of the article 11 can be improved.
[0056] [ka] The perhydropolysilazane contained in the coating liquid 14 may be a mixture of multiple types of perhydropolysilazanes having different polymer structures. For example, perhydropolysilazane may be a mixture of perhydropolysilazane (A) and perhydropolysilazane (B). According to a mixing experiment of these perhydropolysilazane (A) and perhydropolysilazane (B), it was confirmed that a mixture ratio of 50 mass% of perhydropolysilazane (A) and 50 mass% of perhydropolysilazane (B) exhibited rust prevention properties equal to or greater than that of perhydropolysilazane (A) alone, and also shortened the curing time (the time to form the organic / inorganic hybrid coating film 13) compared to perhydropolysilazane (B) alone.
[0057] The organopolysilazane has a hydrogen atom in R and R in the above general formula (Chemical Formula 4), and an organic group in R. - (R SiHNH)- is a repeating unit, and the polysilazane has a cyclic structure with a degree of polymerization of 3 to 5. The polysilazane having both a chain structure and a cyclic structure in the molecule represented by the chemical formula of (R SiHNH) (0.4 < X < 1), the polysilazane having a hydrogen atom in R and organic groups in R and R in the above general formula (Chemical Formula 4), and the polysilazane having organic groups in R and R and a hydrogen atom in R, and having - (R R SiNR )- as a repeating unit, mainly has a cyclic structure with a degree of polymerization of 3 to 5. 1 and R 2 has a hydrogen atom, and R 3 has an organic group. - (R SiHNH)- is a repeating unit, and the polysilazane has a cyclic structure with a degree of polymerization of 3 to 5. The polysilazane having both a chain structure and a cyclic structure in the molecule represented by the chemical formula of (R SiHNH) (0.4 < X < 1), the polysilazane having a hydrogen atom in R and organic groups in R and R in the above general formula (Chemical Formula 4), and the polysilazane having organic groups in R and R and a hydrogen atom in R, and having - (R R SiNR )- as a repeating unit, mainly has a cyclic structure with a degree of polymerization of 3 to 5. 2 SiHNH)- as a repeating unit, a polysilazane having a cyclic structure with a degree of polymerization of 3 to 5, (R SiHNH) 3 〔(R x SiH) 2 SiH) 1.5 N〕 1-X (0.4 < X < 1), a polysilazane having both a chain structure and a cyclic structure in the molecule represented by the chemical formula, in the above general formula (Chemical Formula 4), R 1 has a hydrogen atom, R 2 , R 3 has an organic group, a polysilazane, R 1 and R 2 has an organic group, R 3 has a hydrogen atom, and - (R 1 R 2 SiNR 3 )- as a repeating unit, there is a polysilazane mainly having a cyclic structure with a degree of polymerization of 3 to 5.
[0058] For example, the organopolysilazane having a crosslinked structure in the molecule other than the above general formula (Chemical Formula 4) is represented by the following general formula (Chemical Formula 7).
[0059]
Chemical Formula
[0060]
Chemical Formula
[0061] Examples of the monovalent ethylenically unsaturated group include alkenyl groups such as vinyl, allyl, butenyl, pentenyl, and hexenyl. The number of carbon atoms in the alkenyl group is preferably 2 to 8, more preferably 2 to 6, and even more preferably 2 to 3. Examples of the monovalent ethylenically unsaturated group include (meth)acryloyloxyalkyl groups, that is, groups represented by the formula (B): -R 12 -OC(=O)-CR 11 There is also a group represented by =CH2. Specifically, there are an acryloyloxypropyl group and a methacryloyloxypropyl group. 11 is a hydrogen atom or a methyl group, R 12 is an alkanediyl group, preferably an alkanediyl group having from 1 to 5 carbon atoms. Incidentally, (meth)acrylic is used as a general term for acrylic and methacrylic, and (meth)acryloyl is used as a general term for acryloyl and methacryloyl.
[0062] In the monovalent ethylenically unsaturated group, an alkenyl group is preferred, a vinyl group and an allyl group are preferred, and a vinyl group is more preferred. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl and heptyl groups; aryl groups such as phenyl, tolyl and xylyl groups; and aralkyl groups such as benzyl and phenethyl groups. The number of carbon atoms in the monovalent hydrocarbon group is preferably 1 or more and 8 or less, more preferably 1 or more and 5 or less, and even more preferably 1 or more and 3 or less.
[0063] Examples of monovalent substituted hydrocarbon groups include the 3-mercaptopropyl group (-(CH2)3-SH) and the 3-aminopropyl group (-(CH2)3-NH2). 1 From the viewpoint of fine particle formation, each of them is preferably independently an alkyl group or an alkenyl group, more preferably, each of them is independently an alkyl group having 1 to 3 carbon atoms, a vinyl group, or an allyl group, and even more preferably, a methyl group or a vinyl group.
[0064] In one molecule of the organopolysiloxane having the average unit formula (A), at least a portion of R 1 is a group containing a functional group (L) such as a monovalent ethylenically unsaturated group, an aryl group, or an aralkyl group, and is preferably a monovalent ethylenically unsaturated group, and more preferably an alkenyl group. The total proportion of the monovalent ethylenically unsaturated group, the aryl group, or the aralkyl group is determined based on the total R 1 Based on this, it is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, still more preferably 80 mol % or more, and particularly preferably 90 mol % or more. The monovalent ethylenically unsaturated group, aryl group, or aralkyl group is a hydrophobic group containing a nonionic functional group capable of coordinating to a metal ion.
[0065] In the average unit formula (A), a, b, c, and d represent each constituent unit (R 1 3SiO 1 / 2 ), (R 1 2SiO 2 / 2 ), (R 1 SiO3 / 2 ) and (SiO 4 / 2 The sum of the mole fractions of each structural unit, a, b, c, and d, is 1. a is R 1 3SiO 1 / 2 a is the molar fraction of siloxane units represented by (M units). a is from 0 to 0.5, preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and particularly preferably 0.1 or less.
[0066] b is R 1 2SiO 2 / 2 is the mole fraction of siloxane units represented by (D units). b is 0 or more and 0.5 or less, preferably 0.4 or less, more preferably 0.3 or less, further preferably 0.2 or less, and particularly preferably 0.1 or less. c is R 1 SiO 3 / 2 is the mole fraction of siloxane units represented by (T units). c is 0.3 or more and 1 or less, preferably 0.4 or more, 0.5 or more, or 0.6 or more, more preferably 0.7 or more, still more preferably 0.8 or more, and particularly preferably 0.9 or more.
[0067] d is SiO 4 / 2 is the mole fraction of siloxane units represented by (Q units). d is 0 or more and 0.7 or less, preferably 0.6 or less, 0.5 or less, or 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and particularly preferably 0.1 or less. The sum of c and d, which indicates the total of branched constitutional units, is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and particularly preferably 0.9 or more.
[0068] The organopolysiloxane is a polymer having a constitutional unit (R 1 3SiO 1 / 2 In the case where the structural unit (R 1 2SiO 2 / 2 ) and (R 1 SiO 3 / 2The same applies to the R 1 At least part of R 2 In the average unit formula (A), R may have a structural unit replaced with O. 2 is a hydrogen atom or an alkyl group. 2 O represents a hydroxyl group or an alkoxy group bonded to a silicon atom contained in the organopolysiloxane skeleton. Examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. The number of carbon atoms in the alkyl group is preferably 1 or more and 3 or less.
[0069] The above R in each of the structural units 1 At least part of R 2 The amount of the structural unit replaced with O is preferably 0 or more and 0.10 or less, more preferably 0 or more and 0.05 or less, and even more preferably 0 or more and 0.03 or less, relative to the sum of the molar fractions of the structural units, a, b, c, and d, which is 1. The alkoxy group in the structural unit is, for example, an alkoxy group that is a hydrolyzable group contained in an alkoxysilane described later, and remains in the molecule without being hydrolyzed or polycondensed. The hydroxy group in this structural unit is, for example, a hydroxy group that remains in the molecule after the alkoxy group is hydrolyzed without being polycondensed.
[0070] The organopolysiloxane is preferably a silsesquioxane. Silsesquioxane is a polysiloxane having a main chain structure composed of Si-O bonds and a main structural unit (R 1 SiO 3 / 2 ) units, and the c is 0.7 or more. Examples of the silsesquioxane structure include a random structure, a complete cage structure, an incomplete cage structure, and a ladder structure. Among these, silsesquioxanes having a random structure are preferred from the viewpoint of ease of production.
[0071] The structural unit (R 1 3SiO 1 / 2 As the alkoxysilane that forms R 1 3Si(OR2 Specific examples thereof include methoxydimethylvinylsilane, ethoxydimethylvinylsilane, methoxydimethylphenylsilane, and ethoxydimethylphenylsilane; and methoxytrimethylsilane and ethoxytrimethylsilane.
[0072] The structural unit (R 1 2SiO 2 / 2 As the alkoxysilane that forms R 1 2Si(OR 2 ) 2. Specific examples thereof include dimethoxymethylvinylsilane, diethoxymethylvinylsilane, and dimethoxybenzylmethylsilane; as well as dimethoxydimethylsilane, dimethoxydiethylsilane, diethoxydimethylsilane, diethoxydiethylsilane, dipropoxydimethylsilane, and dipropoxydiethylsilane.
[0073] The structural unit (R 1 SiO 3 / 2 As the alkoxysilane that forms R 1 Si(OR 2 )3. Specific examples thereof include trimethoxyvinylsilane, triethoxyvinylsilane, trimethoxyallylsilane, triethoxyallylsilane, (3-(meth)acryloyloxypropyl)trimethoxysilane, and (3-(meth)acryloyloxypropyl)triethoxysilane; as well as methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, and butyltrimethoxysilane. The structural unit (SiO 4 / 2 As the alkoxysilane that forms Si(OR 2 ) 4. Specific examples thereof include tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane.
[0074] The siloxane contained in the coating liquid 13 may be any one of a chain siloxane having a chain skeleton and a cyclic siloxane having a cyclic skeleton, or a mixture of two or more of them. Examples of the cyclic siloxane include hexamethylcyclotrisiloxane (CH 18 O3Si4), Octamethylcyclotetrasiloxane (C6H 24 O4Si4), decamethylcyclopentasiloxane (C 10 H 30 O5Si5), or a mixture of two or more of them can be used. The organic polysilazane has a number average molecular weight in the range of 3000 to 150000 g / mol.
[0075] The alkyl silicate condensate is one selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetra-n-propyl orthosilicate, tetra-i-propyl orthosilicate, tetra-n-butyl orthosilicate, tetra-sec-butyl orthosilicate, methyl polysilicate, and ethyl polysilicate, or a condensate (mixture) of two or more of them. The inert organic solvent is inert to the organic polysilazane and siloxane, and the alkyl silicate condensate, and is selected from dibutyl ether, turpentine oil, benzene, toluene, xylene, and propylene glycol monomethyl ether acetate.
[0076] Since the number average molecular weight of the organopolysiloxane and the number average molecular weight of the organic polysilazane are within the above ranges, the coating liquid 13 containing the organopolysiloxane and / or the organic polysilazane can maintain a predetermined viscosity, and an organic / inorganic hybrid coating film 10 can be formed from the coating liquid 13. Since the coating liquid 13 is coated on the surface 12 of the substrate 11 (molded product) to be coated while maintaining a predetermined viscosity, even if the coating liquid 13 is coated on the surface 12 of the substrate 11 on which minute holes or meshes are formed, the coating liquid 13 does not penetrate into the substrate 11, and an organic / inorganic hybrid coating film 10 having a substantially uniform thickness can be formed on the surface 12 of the substrate 11.
[0077] In the coating liquid 13, the mixing ratio of the organosilicon material (organopolysiloxane and / or organic polysilazane) to the total mass of the coating liquid 13 is in the range of 30 to 60 mass%, the mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 13 is in the range of 10 to 15 mass%, and the mixing ratio of the inert organic solvent to the total mass of the coating liquid 13 is in the range of 30 to 60 mass%. If the mixing ratio of the organosilicon material (organopolysiloxane and / or organic polysilazane) is less than 30 mass%, the content of the organosilicon material is small, and it is not possible to form an organic / inorganic hybrid coating film 10 of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the substrate 11 (molded product). If the mixing ratio of the organosilicon material (organopolysiloxane and / or organic polysilazane) exceeds 60 mass%, the viscosity of the coating liquid 13 increases more than necessary, and the thickness of the organic / inorganic hybrid coating film 10 becomes larger than necessary. Since the coating liquid 13 has a mixing ratio of the organosilicon material (organopolysiloxane and / or organopolysilazane) within the above-mentioned range relative to the total mass, it is possible to produce an organic / inorganic hybrid coating film 10 of an appropriate thickness that has excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the substrate 11.
[0078] If the blending ratio of the alkyl silicate condensate is less than 10 mass%, the alkyl silicate condensate has a weak effect as a crosslinking agent, and a sufficient crosslinked structure is not formed in the organic / inorganic hybrid coating film 10. If the blending ratio of the alkyl silicate condensate exceeds 15 mass%, an unnecessary crosslinked structure is formed in the organic / inorganic hybrid coating film 10, and the flexibility of the organic / inorganic hybrid coating film 10 becomes greater than necessary. Since the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid 13 is within the above range, the coating liquid 13 can be used to produce an organic / inorganic hybrid coating film 10 having an appropriate crosslinked structure and appropriate flexibility.
[0079] If the blending ratio of the inert organic solvent is less than 30% by mass, the viscosity of the coating liquid 13 becomes high, and the thickness of the organic / inorganic hybrid coating film 10 made from the coating liquid 13 becomes larger than necessary. If the blending ratio of the inert organic solvent exceeds 60% by mass, the viscosity of the coating liquid 13 becomes lower than necessary, and it is not possible to form an organic / inorganic hybrid coating film 10 of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the substrate 11 (molded product). Since the blending ratio of the inert organic solvent to the total mass of the coating liquid 13 is within the above range, it is possible to form an organic / inorganic hybrid coating film 10 of an appropriate viscosity having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the substrate 11 using the coating liquid 13.
[0080] The coating liquid 13 contains an organosilicon material (organopolysiloxane and / or organic polysilazane) in the range of 30 to 60 mass % and an alkyl silicate condensate in the range of 10 to 15 mass % relative to its total mass, so that the formation (film formation) rate of the organic / inorganic hybrid coating film 10 made from the coating liquid 13 can be appropriately controlled. Specifically, the hydrolysis of the alkyl silicate condensate proceeds faster than the condensation of the organopolysiloxane and / or organic polysilazane, so that the progress of the condensation reaction of the organopolysiloxane and / or organic polysilazane can be delayed by first consuming a portion of water (H2O) in the hydrolysis of the alkyl silicate condensate, and the formation (film formation) rate of the organic / inorganic hybrid coating film 10 can be controlled. In addition, since the hydrolysis of the alkyl silicate condensate occurs first, a crosslinked structure can be reliably formed in the organic / inorganic hybrid coating film 10 to impart flexibility.
[0081] In addition, since the organic solvent is selected from dibutyl ether, turpentine oil, benzene, and toluene, which are inactive against organic polysilazane, siloxane, and alkyl silicate condensates, the condensation reaction of organopolysiloxane and / or organic polysilazane does not proceed rapidly, and it is possible to appropriately control the formation (film formation) rate of the organic / inorganic hybrid coating film 10. The coating liquid 13 capable of controlling the formation (film formation) rate of the organic / inorganic hybrid coating film 10 can easily perform the coating operation on the surface 12 of the substrate 11 (molded product).
[0082] The glass particles 14 mixed in the coating liquid 13 are silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+) is a conductive glass containing at least one or more kinds of metal ions 15 from among silver ions 15a, copper ions 15b, and zinc ions 15c. Glass particles 14 (conductive glass) containing metal ions 15 of silver ions 15a, copper ions 15b, and zinc ions 15c exhibit ionic conductivity. Glass particles 14 include glass particles (not shown) based on at least one or more kinds of vanadium oxide (VO) (electronically conductive glass), tungsten oxide (WO) (electronically conductive glass), and molybdenum oxide (MoO) (electronically conductive glass), and phosphorus oxide (PO) (electronically conductive glass).
[0083] An example of the glass particles 14 is silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and at least one of the above. Another example of the glass particles 14 is a conductive glass (electron conductive glass) containing silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and a glass based on at least one of vanadium oxide (VO), tungsten oxide (WO), and molybdenum oxide (MoO), and phosphorus oxide (PO).
[0084] Another example of the glass particles 14 is silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ) and copper ion 15b (Cu 2+) and zinc ion 15c (Zn 2+ ) and vanadium oxide (VO) and phosphorus oxide (PO)-based glass. Another example of the glass particles 14 is a conductive glass (electron-conductive glass) formed from glass particles 14 (conductive glass) containing at least one of silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and glass based on tungsten oxide (WO3) and phosphorus oxide (P2O5). Another example of the glass particles 14 is a conductive glass (electron-conductive glass) formed from glass particles 14 (conductive glass) containing at least one of silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and a glass based on molybdenum oxide (MoO3) and phosphorus oxide (P2O5).
[0085] Another example of the glass particles 14 is silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) is a conductive glass (electronically conductive glass). Another example of the glass particles 14 is a conductive glass containing only silver ions (Ag + Another example of the glass particles 14 is a conductive glass (electronically conductive glass) containing only silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + The conductive glass (electronically conductive glass) is formed from glass particles 14 (conductive glass) containing only vanadium oxide (V2O5), tungsten oxide (WO3), and molybdenum oxide (MoO3) and glass based on phosphorus oxide (P2O5).
[0086] Another example of the glass particles 14 is silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + ) and a conductive glass (electronically conductive glass) formed from glass based on vanadium oxide (V2O5) and phosphorus oxide (P2O5). Another example of the glass particles 14 is a conductive glass (electronically conductive glass) formed from glass based on silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + ) and conductive glass (electronically conductive glass) formed from glass based on tungsten oxide (WO3) and phosphorus oxide (P2O5). Another example of glass particles 14 is a conductive glass (electronically conductive glass) formed from glass based on silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag +) and a conductive glass (electronically conductive glass) formed from glass based on molybdenum oxide (MoO3) and phosphorus oxide (P2O5). Another example of the glass particles 14 is a conductive glass (electronically conductive glass) formed from glass based on silver ions 15a (Ag + The glass particles 14 may contain barium oxide (BaO).
[0087] Silver ion 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) are in an unstable state (positively charged), so they are taken into the cells of microorganisms (viruses, bacteria, fungi, algae, etc.) to bind with the oxygen. The taken-up silver ions 15a, copper ions 15b, and zinc ions 15c bind to proteins, etc., inhibiting their function and preventing cell division, etc. The dysfunction of the proteins generates reactive oxygen species, which causes the microbial cells to die.
[0088] The coating liquid 13 (organic and inorganic hybrid polymer) is coated or sprayed onto the surface 12 of the substrate 11 (molded product) to be coated, and chemically reacts with moisture to form (deposit) a single-layer or multi-layer ultra-thin organic / inorganic hybrid coating film 10. The organic / inorganic hybrid coating film 10 is deposited as a coating having an average thickness in the range of 0.2 μm to 20 μm, preferably 0.5 μm to 20 μm.
[0089] There is no particular limitation on the method of coating the surface 12 (contact surface) of the substrate 11 (molded product) with the coating liquid 13, and the substrate 11 is coated (covered) by a coating method suited to the shape of the substrate 11. For example, the substrate 11 may be coated by a spray method, a dipping method, a brush coating method, a roll coating method, a gravure coating method, a flexography method, an inkjet method, or the like. There is no particular limitation on the amount of the coating liquid 13 to be applied (amount applied), and the amount of coating is determined according to the surface performance required for the substrate 11 (molded product) to be coated. Generally, the amount is 0.1 to 20 g / m in terms of solid content. 2 The coating amount is 0.1g / m 2 If the coating amount is less than 20 g / m, the organic / inorganic hybrid coating film 10 having the desired properties is not formed. 2 If it exceeds this value, the thickness of the organic / inorganic hybrid coating film 10 increases more than necessary, and the organic / inorganic hybrid coating film 10 loses its flexibility.
[0090] In addition, as a pretreatment step prior to the coating step of the coating liquid 13, water (H2O) such as purified water may be sprayed onto the surface 12 of the substrate 11 (molded product) to adhere the water to the surface 12 of the substrate 11. By doing so, a chemical reaction between the water adhered to the surface 12 of the substrate 11 and the components contained in the coating liquid 13 is promoted, and an organic / inorganic hybrid coating film 10 can be rapidly produced on the surface 12 of the substrate 11, and a strong organic / inorganic hybrid coating film 10 can be formed on the surface 12 of the substrate 11.
[0091] Furthermore, a coating liquid containing inorganic polysilazane as a main component can be coated as a primer on the surface 12 of the substrate 11 (molded product) as a pretreatment step prior to the coating step of the coating liquid 13. For example, when a solution of inorganic polysilazane (1 wt % solution) is coated and then the coating liquid 13 is coated, the rust prevention (durability) of the organic / inorganic hybrid coating film 10 is improved compared to when only the coating liquid 13 is simply coated.
[0092] The mechanism by which the organic / inorganic hybrid coating film 10 is formed on the surface 12 of the substrate 11 is as follows. In the formation (film formation) of the organic / inorganic hybrid coating film 10, the surface 12 of the substrate 11 is coated with the coating liquid 13 by a coating process, and then the surface 12 of the substrate 11 is left at room temperature (normal temperature) for a predetermined time (24 hours or more) without heating. Alternatively, the surface 12 of the substrate 11 is coated with the coating liquid 13, and then the surface 12 of the substrate 11 is left at room temperature (normal temperature) for a predetermined time (24 hours or more) while irradiating the surface 12 of the substrate 11 with ultraviolet rays. Alternatively, the surface 12 of the substrate 11 is coated with the coating liquid 13, and then the surface 12 of the substrate 11 is heated to a temperature of less than 400° C. by irradiating the surface 12 of the substrate 11 with infrared rays while irradiating the surface 12 of the substrate 11 with ultraviolet rays, and then left for a predetermined time (24 hours or more).
[0093] A small amount of moisture (water droplets) is attached to the surface 12 of the substrate 11 due to condensation or humidity in the air (including the case where water (H2O) is sprayed). When the surface 12 of the substrate 11 is coated with the coating liquid 13 in a thin film form by a coating process, organopolysiloxane contained in the coating liquid 13 is formed (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 SiO 3 / 2 ) c (SiO 4 / 2 ) d reacts chemically with moisture (H20) in the air, or reacts with -(SiR 1 R 2 -NR 3 )-unit components and / or -(SiR 1 R 2 -NR 3The siloxane bond (Si-O-Si) is bonded to the main chain of the surface 12 of the substrate 11 through a chemical reaction of the siloxane unit components with moisture (H20) in the air, forming an organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain of the siloxane bond (Si-O-Si). Furthermore, the above chemical reaction generates a small amount of gas (NH3, H2) as a by-product. These gases do not remain on the surface 12 of the article 11, but are volatilized (released) into the atmosphere.
[0094] As shown in FIG. 2(b), the coating liquid 13 containing organopolysiloxane and / or organic polysilazane undergoes a chemical reaction (deammonia crosslinking) with moisture contained in the air in the surface layer 16 in contact with the air, and gases such as hydrogen and ammonia, which are by-products of the organic / inorganic hybrid coating film 10, volatilize from the surface 12 (surface layer 16) to the outside air, and a coating layer 17 is formed (generated) on the surface 12 side of the organic / inorganic hybrid coating film 10. The coating liquid 13 coated on the surface 12 of the substrate 11 undergoes a chemical reaction (deammonia crosslinking) with moisture (water droplets) attached to the surface 12 or hydroxyl groups -OH (see FIG. 7) present as terminals on the surface in the back layer 18 in contact with the surface 12 of the substrate 11, and gases such as hydrogen and ammonia rise in the coating layer 17 and volatilize from the surface 12 (surface layer 16) to the outside air, and a coating layer 17 is formed (generated) on the back side 18 of the organic / inorganic hybrid coating film 10.
[0095] First, a coating layer 17 (a vitrified (inorganized) portion and an organic portion) is generated in the surface layer 16 and the back layer 18 of the coating liquid 13. Next, the coating layer 17 (a vitrified (inorganized) portion and an organic portion) is formed and expanded from the surface layer 16 side toward the back layer 18 side, and the coating layer 17 (a vitrified (inorganized) portion and an organic portion) is expanded from the back layer 18 side toward the surface layer 16 side, so that the coating layer 17 (a vitrified (inorganized) portion and an organic portion) of the intermediate layer 19 is successively formed (generated), and finally, an organic / inorganic hybrid coating film 10 is formed (generated) on the surface layer 16 in contact with the outside air, the back layer 18 in contact with the surface 12 of the substrate 11, and the intermediate layer 19 between the surface layer 16 and the back layer 18.
[0096] Immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, as shown in FIG. ,5 As shown in FIG. 1, glass particles 14 mixed in the coating liquid 13 are dispersed and mixed inside the coating liquid 13, and silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 are not diffused toward the surface of the coating liquid. Specifically, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, the silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ), and electronically conductive glass formed from glass based on at least one of vanadium oxide (VO), tungsten oxide (WO), and molybdenum oxide (MoO) and phosphorus oxide (PO). + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 do not diffuse toward the surface layer 16 (surface) of the coating liquid 13.
[0097] In the cross-sectional view shown in FIG. + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) are dispersed and mixed in the coating liquid 13. As described above, the glass particles 14 are doped with silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and silver ion 15a (Ag + ), and copper ions (Cu 2+ ) or zinc ion (Zn 2+ ) is contained. In the cross-sectional view shown in FIG.+ ) and copper ions 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) are dispersed and mixed in the coating liquid 13. As described above, the glass particles 14 (conductive glass) containing only silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + ) are dispersed and mixed in the coating liquid 13.
[0098] Specifically, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ), and electronically conductive glass formed from glass based on vanadium oxide (VO) and phosphorus oxide (PO). + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13. Also, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, the silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and at least 1 Glass particles 14 (conductive glass) containing one or more kinds of metal ions 15 and electronically conductive glass formed from glass based on tungsten oxide (WO3) and phosphorus oxide (P2O5) are dispersed and mixed inside the coating liquid 13. Silver ions 15a (Ag + ) and copper ion 15b (Cu2+ ), zinc ion 15c (Zn 2+ ) do not diffuse toward the surface layer 16 (surface) of the coating liquid 13. + ) and copper ion 15b (Cu 2+ ) and zinc ion 15c (Zn 2+ ) and at least 1 Glass particles 14 (conductive glass) containing one or more kinds of metal ions 15 and electronically conductive glass formed from glass based on molybdenum oxide (MoO3) and phosphorus oxide (P2O5) are dispersed and mixed inside the coating liquid 13. Silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13.
[0099] Furthermore, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + ), and conductive glass (electronically conductive glass) formed from glass based on vanadium oxide (V2O5) and phosphorus oxide (P2O5), are dispersed and mixed inside the coating liquid 13. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13. Also, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, the silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag +), and conductive glass (electronically conductive glass) formed from glass based on tungsten oxide (WO3) and phosphorus oxide (P2O5), are dispersed and mixed inside the coating liquid 13. Silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13.
[0100] Immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, silver ions 15a (Ag + ) Conductive glass containing only copper ions 15b (Cu 2+ ) containing only zinc ions, 15C (Zn 2+ ) among conductive glasses containing only silver ions 15a (Ag + ), and conductive glass (electronically conductive glass) formed from glass based on molybdenum oxide (MoO3) and phosphorus oxide (P2O5), are dispersed and mixed inside the coating liquid 13. Silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13. Also, immediately after the coating liquid 13 is applied to the surface 12 of the substrate 11, the silver ions 15a (Ag + ) are dispersed and mixed inside the coating liquid 13, and silver ions 15a (Ag + ) does not diffuse toward the surface layer 16 (surface) of the coating liquid 13.
[0101] In the process of forming (forming) an organic / inorganic hybrid coating film 10 from organopolysiloxane and / or organic polysilazane, as shown in FIGS. 4 and 6, after a coating liquid 13 is coated on a surface 12 of a substrate 11, silver ions 15a (Ag +) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) migrates inside the coating liquid 13 and silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 diffuse inside the coating film 10 toward a surface layer 16 (surface) of the organic / inorganic hybrid coating film 10 .
[0102] The organic / inorganic hybrid coating film 10 made of organopolysiloxane and / or organic polysilazane is formed of a glass coating layer (amorphous glass coating layer) and an organic coating layer. The organic / inorganic hybrid coating film 10 is mainly composed of SiO2 generated by reacting organopolysiloxane and / or organic polysilazane, and thus a coating layer 17 that is easy to spread in a plane and has high density and high hardness (pencil hardness of about 6H to 9H) is formed. Silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 are diffused.
[0103] After the coating liquid 13 is applied to the surface 12 of the substrate 11, silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 diffuse within the coating film 10 from the back layer 18 (bottom) of the organic / inorganic hybrid coating film 10 toward the surface layer 16 (surface), so that silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) The organic / inorganic hybrid coating film 10 exhibits antibacterial, antiviral, antifungal and deodorizing functions due to metal ions 15.
[0104] The organic / inorganic hybrid coating film 10 is formed into a thin film by the coating liquid 13 containing organopolysiloxane and / or organic polysilazane. The average thickness of the organic / inorganic hybrid coating film 10 is in the range of 0.2 μm to 20 μm, preferably in the range of 0.5 μm to 20 μm. If the average thickness of the organic / inorganic hybrid coating film 10 is less than 0.2 μm, the strength of the organic / inorganic hybrid coating film 10 decreases and the protective function is lost, and the surface 12 of the substrate 11 cannot be sufficiently protected. If the average thickness of the organic / inorganic hybrid coating film 10 exceeds 20 μm, the flexibility of the organic / inorganic hybrid coating film 10 decreases, and the organic / inorganic hybrid coating film 10 may peel off from the surface 12 due to deformation of the surface 12 of the substrate 11. Although the organic / inorganic hybrid coating film 10 is a coating film whose main component is SiO2, it has excellent flexibility, and coupled with the anchoring effect of the anchor parts 20, it will not peel off even if the surface 12 of the substrate 11 is made of a cloth material, nonwoven fabric, or the like that causes deformation, and can maintain the coating state of the organic / inorganic hybrid coating film 10 by following the deformation of the surface 12.
[0105] As shown in an example of the structure image of the organic / inorganic hybrid coating film 10 in Fig. 5, a hydrolysis product having a -(Si(OH)2-O-Si(OH)2)- unit generated by chemically reacting an alkyl silicate condensate with water causes a crosslinking reaction with a part of the main chain of the siloxane bond (Si-O-Si) in each coating layer 17 (surface layer 16, intermediate layer 19, back layer 18), forming a crosslinked structure, which is assumed to give the organic / inorganic hybrid coating film 10 a dense and flexible structure. In addition, it is assumed that the formation of a crosslinked structure allows the coordination of a hydrophobic methyl group (CH3) derived from the organopolysiloxane and / or organic polysilazane and a hydrophilic hydroxyl group (OH) derived from the hydrolysis product of the alkyl silicate condensate on the surface of the organic / inorganic hybrid coating film 10.
[0106] Unless a special surface treatment such as mirror finishing is performed, the surface 12 of the substrate 11 before being coated with the organic / inorganic hybrid coating film 10 has many microscopic irregularities formed due to small scratches and the like occurring during the manufacturing process, etc. When the coating liquid 13 is coated onto the surface 12 of the substrate 11 and hardens while penetrating into the irregularities, the anchor parts 20 of the organic / inorganic hybrid coating film 10 that have hardened and penetrated into the irregularities exert an anchor effect, and the organic / inorganic hybrid coating film 10 adheres more firmly to the surface 12 of the substrate 11.
[0107] When the surface 12 of the substrate 11 is a smooth surface with almost no unevenness, the surface 12 may be roughened to form unevenness with an average roughness of about 1 to 500 μm on the surface 12 as a pretreatment for coating with the coating liquid 13. By performing the roughening treatment in this manner, an anchor effect can be obtained by the anchor portion 20 of the organic / inorganic hybrid coating film 10. After the roughening treatment, a cleaning treatment is performed in which metal powder, plastic powder, etc. generated on the surface of the substrate is blown away using an air injection means such as an air gun. After the cleaning treatment, a predetermined time is left to cause condensation, etc. to occur on the surface 12 of the substrate 11, and naturally occurring moisture is attached to the surface.
[0108] In this case, after the surface 12 of the substrate 11 is roughened and cleaned, moisture is actively applied to the surface 12 on which the unevenness is formed by the roughening using a moisture applying means such as a sprayer, and then the coating liquid 13 is coated. In this manner, it is possible to promote a chemical reaction between the moisture applied to the surface 12 of the substrate 11 and the coating liquid 13 in contact with the surface 12. It is also possible to apply moisture using a moisture applying means without performing a roughening treatment on the surface 12 of the substrate 11. Since the unevenness initially formed on the surface 12 of the substrate 11 before being coated with the organic / inorganic hybrid coating film 10 made of organopolysiloxane and / or organic polysilazane is covered by the organic / inorganic hybrid coating film 10, the surface 12 is formed smoother after coating than before coating.
[0109] As shown in FIG. 7, the organic / inorganic hybrid coating film 10 formed on the surface 12 of the substrate 11 has a porous structure, so that silver ions 15a (Ag + ), copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can move inside the organic / inorganic hybrid coating film 10, and the metal ions 15 are eluted from the organic / inorganic hybrid coating film 10.
[0110] In the organic / inorganic hybrid coating film 10, the content of the glass particles 14 diffused and mixed therein is in the range of 0.1 volume % to 30 volume %, preferably in the range of 1 volume % to 10 volume %. If the content of the glass particles 14 diffused and mixed in the organic / inorganic hybrid coating film 10 is less than 0.1 volume %, the content of the glass particles 14 in the organic / inorganic hybrid coating film 10 is small, and the organic / inorganic hybrid coating film 10 cannot exhibit sufficient antibacterial / antiviral function, antifungal function, and deodorizing function. If the content of the glass particles 14 diffused and mixed in the organic / inorganic hybrid coating film 10 exceeds 30 volume %, the adhesion of the organic / inorganic hybrid coating film 10 to the surface 12 of the substrate 11 is significantly reduced, and a smooth organic / inorganic hybrid coating film 10 cannot be formed on the surface 12.
[0111] The organic / inorganic hybrid coating film 10 has excellent antibacterial, antiviral, antifungal and deodorizing functions, and the antibacterial, antiviral, antifungal and deodorizing functions are maintained for a long period of time because the content of the glass particles 14 dispersed and mixed therein is within the above range. Furthermore, the organic / inorganic hybrid coating film 10 has high adhesion to the surface 12 of the substrate 11, and can form a smooth thin film on the surface 12 of the substrate 11.
[0112] In the organic / inorganic hybrid coating film 10, the average particle size D 50 The average particle diameter D of the glass particles 14 in the organic / inorganic hybrid coating film 10 is 5 μm or less, preferably 3 μm or less. 50When the thickness of the coating liquid 13 exceeds 5 μm, silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) cannot sufficiently diffuse inside the coating film 10 toward the surface layer 16 (surface) of the organic / inorganic hybrid coating film 10, and the organic / inorganic hybrid coating film 10 cannot exhibit sufficient antibacterial, antiviral, antifungal and deodorizing functions. Furthermore, the adhesion of the organic / inorganic hybrid coating film 10 to the surface 12 of the substrate 11 is significantly reduced, and a smooth organic / inorganic hybrid coating film 10 cannot be formed on the surface 12. The organic / inorganic hybrid coating film 10 has an average particle size D 50 Since the viscosity is within the above range, the composition has excellent antibacterial, antiviral, antifungal and deodorizing functions, and the antibacterial, antiviral, antifungal and deodorizing functions are maintained for a long period of time. Furthermore, the composition has high adhesion to the surface 12 of the substrate 11, and can form a smooth thin film on the surface 12 of the substrate 11.
[0113] In the organic / inorganic hybrid coating film 10 (coating film), since the glass particles 15 have electronic conductivity, a large amount of silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be introduced, and the organic / inorganic hybrid coating film 10 can contain a large amount of metal ions 15 such as silver ions 15a, copper ions 15b, and zinc ions 15c.
[0114] The organic / inorganic hybrid coating film 10 (coating film) contains a large amount of silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+) metal ions 15, it has excellent antibacterial, antiviral and antifungal properties as well as deodorizing properties, and can reliably kill germs, various viruses and various mold spores, and can reliably eliminate unpleasant odors.
[0115] The organic / inorganic hybrid coating film 10 (coating film) is not limited to the object to be coated, and can impart excellent antibacterial, antiviral, antifungal and deodorizing functions to the surface 12 of any substrate 11 (object to be coated). It also contains a large amount of silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15, the antibacterial, antiviral, antifungal and deodorizing functions can be sustained for a long period of time.
[0116] When the organic / inorganic hybrid coating film 10 (coating film) in which the glass particles 14 are diffused and mixed is formed (formed) on medical clothing (masks, white coats, protective clothing, gloves, etc.) or medical bedding (futons, pillowcases, curtains, patient amenities, etc.), even if various germs, various viruses, and various molds adhere to the medical clothing or medical bedding, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be used to convert the various germs, viruses, and molds into silver ions. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be killed by the metal ions 15, thereby preventing the occurrence and proliferation of germs, various viruses, and various molds in medical clothing and medical bedding, and preventing the occurrence of unpleasant odors in medical clothing.
[0117] When the organic / inorganic hybrid coating film 10 (coating film) in which the glass particles 14 are diffused and mixed is formed (formed) on medical instruments (scissors, scalpels, other equipment, etc.) or hospital facilities (handrails, doorknobs, walls, floors, elevators, escalators, etc.), even if germs, various viruses, and various mold bacteria adhere to the medical instruments and enter the hospital facilities, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be easily removed. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be killed by metal ions 15, which can prevent the occurrence and proliferation of germs, various viruses, and various molds in medical instruments and hospital facilities, and can prevent biohazards in medical institutions as well as the occurrence of unpleasant odors in medical institutions.
[0118] When the organic / inorganic hybrid coating film 10 (coating film) in which the glass particles 14 are diffused and mixed is formed (formed) on a means of transportation (train, bus, airplane, ship, vehicle, etc.), even if various germs, various viruses, and various mold fungi enter the means of transportation, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be used to convert the various germs, viruses, and various mold fungi into silver ions. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be killed by the metal ions 15, and the occurrence and proliferation of germs, various viruses, and various molds in the means of transportation can be prevented, and infection with germs and various viruses in the means of transportation can be prevented.
[0119] When an organic / inorganic hybrid coating film 10 (coating film) in which glass particles 14 are diffused and mixed is formed (formed) on clothing (underwear, T-shirts, socks, sportswear, diapers, etc.), even if various germs, various viruses, and various mold fungi adhere to the clothing, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be used to convert the various germs, viruses, and mold fungi into silver ions. + ) and copper ion 15b (Cu 2+), zinc ion 15c (Zn 2+ ) can be killed by metal ions 15, which can prevent the occurrence and proliferation of germs, various viruses, and various molds on clothes, as well as prevent the occurrence of unpleasant odors on clothes.
[0120] When an organic / inorganic hybrid coating film 10 (coating film) in which glass particles 10 are diffused and mixed is formed (formed) on a pet product (pet toilet, pet cage, etc.), even if various germs, various viruses, and various mold fungi adhere to the pet product, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be used to convert the various germs, viruses, and various mold fungi into silver ions. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be killed by metal ions 15, which can prevent the occurrence and proliferation of germs, various viruses, and various molds in pet products, as well as prevent the infection of pets with germs and various viruses.
[0121] When the organic / inorganic hybrid coating film 10 (coating film) in which the glass particles 14 are diffused and mixed is formed (formed) on sanitary products (kitchen products, toilet products, bath products, washstands, etc.) or food products (food trays, kitchen products, tableware, etc.), even if various germs, various viruses, and various mold bacteria adhere to the sanitary products or food products, the silver ions 15a (Ag ions) diffused into the organic / inorganic hybrid coating film 10 can be used to convert the various germs, viruses, and mold bacteria into silver ions. + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) can be killed by the metal ions 15, thereby preventing the occurrence and proliferation of germs, various viruses, and various molds in sanitary products and food products, and allowing the sanitary products and food products to be used hygienically.
[0122] FIG. 9 is a diagram showing the relationship between time and antiviral activity value in an organic / inorganic hybrid coating film 10 formed from coating liquid 13 containing organopolysiloxane (siloxane-based solution) as the main component and glass particles 14 mixed therein, and FIG. 10 is a graph showing the change in antiviral activity value over time after coating liquid 13 containing organopolysiloxane (siloxane-based solution) as the main component and glass particles 14 mixed therein is applied to surface 12 of substrate 11.
[0123] A coating liquid 13 containing organopolysiloxane (siloxane-based solution) as the main component and glass particles 14 mixed therein was applied to a surface 12 of an acrylic substrate 11 (base material 11) (50 × 50 × 5 mm), and an organic / inorganic hybrid coating film 10 was formed on the surface 12 of the acrylic substrate 11. As described above, the film formation conditions are as follows: after coating the surface 12 of the acrylic substrate 11 (base material 11) with the coating liquid 13, the surface 12 of the acrylic substrate 11 (base material 11) is left at room temperature (normal temperature) for a predetermined time (24 hours or more) without heating; or after coating the surface 12 of the acrylic substrate 11 (base material 11) with the coating liquid 13, the surface 12 of the acrylic substrate 11 is left at room temperature (normal temperature) for a predetermined time (24 hours or more) while irradiating the surface 12 of the acrylic substrate 11 with ultraviolet rays; or after coating the surface 12 of the acrylic substrate 11 (base material 11) with the coating liquid 13, the surface 12 of the acrylic substrate 11 is irradiated with infrared rays while irradiating the surface 12 of the acrylic substrate 11 with ultraviolet rays to heat the temperature of the surface 12 of the acrylic substrate 11 to less than 400°C, and then left for a predetermined time (24 hours or more).
[0124] After a coating liquid 13 is applied to a surface 12 of an acrylic substrate 11, an organic / inorganic hybrid coating film 10 is formed (deposited) on the surface 12. The organic / inorganic hybrid coating film 10 formed (deposited) on the surface 12 of the acrylic substrate 11 (base material 11) contains 15% by volume of glass particles 14, and the average particle diameter D 50 is less than 5 μm.
[0125] After coating the acrylic substrate 11 with the coating liquid 13, an enveloped virus (influenza virus (or novel coronavirus, herpes virus, rubella virus)) was inoculated onto the surface 12 of the acrylic substrate 11, and the antiviral activity value against the enveloped virus (influenza virus) was measured over time. The measurement times for the antiviral activity value against the enveloped virus (influenza virus) were 0.5 hours after inoculation of the acrylic substrate 11 with the enveloped virus, 2 hours after inoculation of the acrylic substrate 11 with the enveloped virus, 5 hours after inoculation of the acrylic substrate 11 with the enveloped virus, and 24 hours after inoculation of the acrylic substrate 11 with the enveloped virus.
[0126] In addition, after the acrylic substrate 11 was coated with the coating liquid 13, a non-enveloped virus (feline calicivirus (or rotavirus, norovirus)) was inoculated onto the surface 12 of the acrylic substrate 11, and the antiviral activity value against the non-enveloped virus (feline calicivirus) was measured over time. The measurement times for the antiviral activity value against the non-enveloped virus were 0.5 hours after the acrylic substrate 11 was inoculated with the non-enveloped virus, 2 hours after the acrylic substrate 11 was inoculated with the non-enveloped virus, 5 hours after the acrylic substrate 11 was inoculated with the non-enveloped virus, and 24 hours after the acrylic substrate 11 was inoculated with the non-enveloped virus.
[0127] As shown in Figures 7 and 8, for enveloped viruses (influenza virus, novel coronavirus, herpes virus, rubella virus), 0.5 hours after the acrylic substrate 11 is coated with the coating liquid 13, the antiviral activity value is 0, 2 hours after the acrylic substrate 11 is coated with the coating liquid 13, the antiviral activity value is 0.1, and 5 hours after the acrylic substrate 11 is coated with the coating liquid 13, the antiviral activity value is 0.4, meaning that the antiviral activity (antiviral function) is hardly expressed until 5 hours after the acrylic substrate 11 is coated with the coating liquid 13.
[0128] However, 24 hours after coating the acrylic substrate 11 with the coating liquid 13, the antiviral activity increased to 2.2. An antiviral function is recognized when the antiviral activity is 2 or more. As is clear from Figures 9 and 10, it was found that the organic / inorganic hybrid coating film 10 containing the above-mentioned glass particles 14 has an excellent antiviral function against enveloped viruses 24 hours after coating the acrylic substrate 11 with the coating liquid 13, and can reliably kill various enveloped viruses.
[0129] Furthermore, for non-enveloped viruses (feline calicivirus, rotavirus, norovirus), 0.5 hours after the acrylic substrate 11 was coated with the coating liquid 13, the antiviral activity value was 0, 2 hours after the acrylic substrate 11 was coated with the coating liquid 13, the antiviral activity value was 0.1, and 5 hours after the acrylic substrate 11 was coated with the coating liquid 13, the antiviral activity value was 0.3, indicating that almost no antiviral activity (antiviral function) was expressed until 5 hours after the acrylic substrate 11 was coated with the coating liquid 13.
[0130] However, the antiviral activity increased to 4.5 24 hours after the coating liquid was applied to the acrylic substrate 11. As is clear from Figures 9 and 10, the organic / inorganic hybrid coating film 10 containing the above-mentioned glass particles 14 had an excellent antiviral function against non-enveloped viruses 24 hours after the coating liquid 13 was applied to the acrylic substrate 11, and it was found to be able to reliably kill various non-enveloped viruses.
[0131] FIG. 11 is a diagram showing the antibacterial activity value of an organic / inorganic hybrid coating film 10 formed from a coating liquid 13 containing organopolysiloxane (siloxane-based solution) as the main component and glass particles 14 mixed therein, and FIG. 12 is a graph showing the relationship between the content of glass particles 14 in the organic / inorganic hybrid coating film 10 and the antibacterial activity value.
[0132] In the evaluation of the antibacterial activity value shown in Figures 11 and 12, an acrylic substrate 11(1) (substrate 11) (50 x 50 x 5 mm) on which an organic / inorganic hybrid coating film 10 was not formed (film-formed), a coating liquid 13 containing organopolysiloxane (siloxane-based solution) as the main component and 3 volume % of glass particles 14 mixed therein was applied to a surface 12 of the acrylic substrate 11 (substrate 11) (50 x 50 x 5 mm) and an organic / inorganic hybrid coating film 10 (glass particle 14 content of 3 volume %) was formed on the surface 12 of the acrylic substrate 11 (2), and an acrylic substrate 11(3) on which an organic / inorganic hybrid coating film 10 (glass particle 14 content of 3 volume %) was formed on the surface 12 of the acrylic substrate 11 was applied to a surface 12 of the acrylic substrate 11 (substrate 11) (50 x 50 x 5 mm). The coating liquid 13 was applied to the surface 12 of an acrylic substrate 11 (base material 11) (50×50×5 mm) to form an organic / inorganic hybrid coating film 10 (containing 5% by volume of glass particles 14) on the surface 12 of the acrylic substrate 11 (3), and the coating liquid 13, which is mainly composed of organopolysiloxane (siloxane-based solution) and contains 7% by volume of glass particles 14, was applied to the surface 12 of an acrylic substrate 11 (base material 11) (50×50×5 mm) to form an organic / inorganic hybrid coating film 10 (containing 7% by volume of glass particles 14) on the surface 12 of the acrylic substrate 11 (4). 50 is less than 5 μm.
[0133] As described above, the conditions for forming the organic / inorganic hybrid coating film 10 on the acrylic substrate 11(2) to the acrylic substrate 11(4) are as follows: after the coating liquid 13 is applied to the surfaces 12 of the acrylic substrate 11(2) to the acrylic substrate 11(4) (substrate 11), the surfaces 12 of the acrylic substrate 11(2) to the acrylic substrate 11(4) (substrate 11) are left at room temperature (normal temperature) for a predetermined time (24 hours or more) without heating, or the surfaces 12 of the acrylic substrate 11(2) to the acrylic substrate 11(4) (substrate 11) are left at room temperature (normal temperature) for a predetermined time (24 hours or more). After coating with liquid 13, surfaces 12 of acrylic substrate 11(2) to acrylic substrate 11(4) are irradiated with ultraviolet light while being left at room temperature (normal temperature) for a predetermined time (24 hours or more); alternatively, after coating surfaces 12 of acrylic substrate 11(2) to acrylic substrate 11(4) (substrate 11) with coating liquid 13, surfaces 12 of acrylic substrate 11(2) to acrylic substrate 11(4) are irradiated with infrared light while being irradiated with ultraviolet light to heat surfaces 12 of acrylic substrate 11 to less than 400°C, and then left for a predetermined time (24 hours or more).
[0134] 24 hours have passed since the coating liquid 13 was applied to the surfaces 12 of the acrylic substrates 11 (2) to 11 (4), and an organic / inorganic hybrid coating film 10 has been formed (deposited) on the surfaces 12. The organic / inorganic hybrid coating film 10 deposited on the surface 12 of the acrylic substrate 11 (2) (base material 11) contains 3 volume % glass particles 14, and the average particle diameter D 50 The organic / inorganic hybrid coating film 10 formed on the surface 12 of the acrylic substrate 11 (3) (base material 11) has a glass particle 14 content of 5 volume % and an average particle diameter D 50 The organic / inorganic hybrid coating film 10 formed on the surface 12 of the acrylic substrate 11(4) (base material 11) has a glass particle 14 content of 7 volume % and an average particle diameter D 50After the organic / inorganic hybrid coating film 10 was formed on the surfaces 12 of the acrylic substrates 11(2) to 11(4), Staphylococcus aureus and Escherichia coli were inoculated onto the surfaces 12 of the acrylic substrates 11(1) to 11(4), and the antibacterial activity values against these bacteria were measured.
[0135] As shown in Figures 11 and 12, the antibacterial activity value of acrylic substrate 11(1) against Staphylococcus aureus and against Escherichia coli is 0. If Staphylococcus aureus or Escherichia coli adheres to surface 12 of acrylic substrate 11(1), the Staphylococcus aureus or Escherichia coli cannot be killed, and depending on the conditions, the Staphylococcus aureus or Escherichia coli may grow on acrylic substrate 11(1).
[0136] An acrylic substrate 11(2) on whose surface 12 an organic / inorganic hybrid coating film 10 made from a coating liquid 13 containing 3 volume percent glass particles 14 is formed (deposited) has an antibacterial activity value of 4.7 against Staphylococcus aureus and an antibacterial activity value of 2 against Escherichia coli, which exceeds the antibacterial activity value of 2 or more. Even if Staphylococcus aureus or Escherichia coli adheres to the surface 12 of the acrylic substrate 11(2), the silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 can kill Staphylococcus aureus and Escherichia coli, preventing them from multiplying.
[0137] An acrylic substrate 11(3) on whose surface 12 an organic / inorganic hybrid coating film 10 made from a coating liquid 13 containing 5 volume percent glass particles 14 has been formed (deposited) has an antibacterial activity value of 4.7 against Staphylococcus aureus and an antibacterial activity value of 2 against Escherichia coli, which exceeds the antibacterial activity value of 2 or more. Even if Staphylococcus aureus or Escherichia coli adheres to the surface 12 of the acrylic substrate 11(3), the silver ions 15a (Ag +) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 can kill Staphylococcus aureus and Escherichia coli, preventing them from multiplying.
[0138] An acrylic substrate 11(4) on whose surface 12 an organic / inorganic hybrid coating film 10 made from a coating liquid 13 containing 7 volume percent glass particles 14 is formed (deposited) has an antibacterial activity value of 4.7 against Staphylococcus aureus and an antibacterial activity value of 2 against Escherichia coli, which exceeds the antibacterial activity value of 2 or more. Even if Staphylococcus aureus or Escherichia coli adheres to the surface 12 of the acrylic substrate 11(4), the silver ions 15a (Ag + ) and copper ion 15b (Cu 2+ ), zinc ion 15c (Zn 2+ ) metal ions 15 can kill Staphylococcus aureus and Escherichia coli, preventing them from multiplying.
[0139] As is clear from Figures 11 and 12, it was found that the organic / inorganic hybrid coating film 10 containing the above-mentioned glass particles 14 has excellent antibacterial properties against Staphylococcus aureus and Escherichia coli, achieving an inactivation rate of 99.9999% for Staphylococcus aureus and Escherichia coli, and can reliably kill Staphylococcus aureus and Escherichia coli.
[0140] FIG. 13 is a diagram showing the mold resistance evaluation of an organic / inorganic hybrid coating film formed from a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed therein.
[0141] In the mold resistance evaluation shown in Figure 13, an acrylic substrate (1) (base material) (50 x 50 x 5 mm) on which no organic / inorganic hybrid coating film was formed (film-formed), an acrylic substrate (2) on which a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and 3 volume % of glass particles was applied to the surface of the acrylic substrate (base material) (50 x 50 x 5 mm) and an organic / inorganic hybrid coating film was formed on the surface of the acrylic substrate, and an acrylic substrate (3) on which a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and 5 volume % of glass particles was applied to the surface of the acrylic substrate. A coating liquid containing 7% by volume of glass particles was applied to the surface of an acrylic substrate (base material) (50 x 50 x 5 mm) to form an organic / inorganic hybrid coating film on the surface of the acrylic substrate (3), and an acrylic substrate (4) was prepared by applying a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and 7% by volume of glass particles to the surface of an acrylic substrate (base material) (50 x 50 x 5 mm) to form an organic / inorganic hybrid coating film on the surface of the acrylic substrate. Average particle diameter D of glass particles 50 is less than 5 μm.
[0142] As described above, the film formation conditions for the acrylic substrate (2) to the acrylic substrate (4) are as follows: after the surfaces of the acrylic substrate (2) to the acrylic substrate (4) (substrate) are coated with a coating liquid, the surfaces of the acrylic substrate (2) to the acrylic substrate (4) (substrate) are left at room temperature (normal temperature) for a predetermined time (24 hours or more) without heating them; or, after the surfaces of the acrylic substrate (2) to the acrylic substrate (4) (substrate) are coated with a coating liquid, the surfaces of the acrylic substrate (2) to the acrylic substrate (4) are left at room temperature (normal temperature) for a predetermined time (24 hours or more) while irradiating the surfaces of the acrylic substrate (2) to the acrylic substrate (4) with ultraviolet rays; or, after the surfaces of the acrylic substrate (2) to the acrylic substrate (4) (substrate) are coated with a coating liquid, the surfaces of the acrylic substrate (2) to the acrylic substrate (4) are irradiated with infrared rays while irradiating the surfaces with ultraviolet rays to heat the surfaces of the acrylic substrate to less than 400° C., and then left for a predetermined time (24 hours or more).
[0143] 24 hours have passed since the coating liquid was applied to the surfaces of the acrylic substrates (2) to (4), and an organic / inorganic hybrid coating film has been formed (deposited) on the surfaces. The organic / inorganic hybrid coating film deposited on the surface of the acrylic substrate (2) (base material) contains 3 volume % of glass particles 14, and the average particle diameter D 50 The organic / inorganic hybrid coating film formed on the surface of the acrylic substrate (3) (base material) has a glass particle 14 content of 5 volume % and an average particle diameter D 50 The organic / inorganic hybrid coating film formed on the surface of the acrylic substrate (4) (base material) has a glass particle 14 content of 7 volume % and an average particle diameter D 50 is less than 5 μm.
[0144] After forming an organic / inorganic hybrid coating film on the surfaces of acrylic substrate (2) to acrylic substrate (4), spores of a mixture of five fungal species, Aspergillus niger NBRC 105649, Penicillium pinophilum NBRC 100533, Paecilomyces variotii NBRC 107725, Trichoderna virens NBRC 6355, and Chaetomium globosum NBRC 6347, were inoculated onto the surfaces of acrylic substrate (1) to (4). After culturing the fungi for four weeks, the fungal resistance of acrylic substrate (1) to acrylic substrate (4) was measured. The culture conditions were as follows: acrylic substrate (1) to acrylic substrate (4) were placed on the mineral- and glucose-containing agar medium contained in containers 1 to 4, and a mineral- and glucose-containing mold spore liquid (a mixture of five strains) was sprayed onto the medium. After culturing for four weeks at approximately 29°C and 95% rh or higher, the growth status of the mold in containers 1 to 4 was judged visually and microscopically.
[0145] The mold growth status is evaluated as follows: (5) when the mycelium grows vigorously and the mold covers the entire medium, (4) when the mold area is 50% or more of the total area of the medium under microscope, (3) when the mold area is 50% or more but less than 50% of the total area of the medium under microscope, (2) when the mold area is less than 25% of the total area of the medium under microscope, (1) when mold growth is not visible to the naked eye but can be confirmed under microscope, and (0) when mold growth is not visible to the naked eye or under microscope. Mold resistance is recognized with ratings (0) to (2).
[0146] The evaluation of the acrylic substrate (1) placed on the mineral-glucose-containing agar medium in the first container was (4), and the area of mold was more than 50% of the total area of the medium. The evaluation of the acrylic substrate (2) placed on the mineral-glucose-containing agar medium in the second container, the acrylic substrate (3) placed on the mineral-glucose-containing agar medium in the third container, and the acrylic substrate (4) placed on the mineral-glucose-containing agar medium in the fourth container was (2), and mold resistance was observed in the acrylic substrates (2) to (4). As is clear from Figure 13, it was found that the organic / inorganic hybrid coating film containing the above-mentioned glass particles has excellent mold-proofing properties against mold fungi and can reliably kill various mold fungi.
[0147] Figure 14 is a diagram showing an evaluation of the deodorizing performance of an organic / inorganic hybrid coating film formed from a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed in. In the evaluation of the deodorizing performance shown in Figure 14, the deodorizing performance was evaluated for ammonia, which is the source of sweat odor, aging odor, excrement odor, cigarette odor, and food waste odor, acetic acid, which is the source of sweat odor, aging odor, excrement odor, and cigarette odor, isovaleric acid, which is the source of sweat odor and aging odor, inenal, which is the source of aging odor, methyl mercaptan, which is the source of excrement odor and food waste odor, hydrogen sulfide, which is the source of excrement odor, cigarette odor, and food waste odor, indole, which is the source of excrement odor, pyridine, which is the source of cigarette odor, and trimethylamine, which is the source of food waste odor.
[0148] In the evaluation of the deodorizing performance shown in Figure 14, an aggregate of polyester fibers (1) (substrate) on which no organic / inorganic hybrid coating film was formed (film-formed), and an aggregate of polyester fibers (2) (substrate) in which the polyester fibers (substrate) were impregnated with a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and 7 volume % glass particles mixed therein, were prepared. The average particle diameter D of the glass particles 50 is less than 5 μm.
[0149] The film-forming conditions for the polyester fibers (2) are as follows: after impregnating the polyester fibers (2) (substrate) with the coating liquid, the polyester fibers (2) (substrate) are left at room temperature (normal temperature) for a predetermined time (24 hours or more) without heating the surface of the polyester fibers (2) (substrate), as described above; or, after impregnating the polyester fibers (2) (substrate) with the coating liquid, the polyester fibers (2) are left at room temperature (normal temperature) for a predetermined time (24 hours or more) while irradiating the surface of the polyester fibers (2) with ultraviolet rays; or, after impregnating the polyester fibers (2) (substrate) with the coating liquid, the surface of the polyester fibers (2) is heated to a temperature of less than 400° C. by irradiating infrared rays while irradiating the surface of the polyester fibers (2) with ultraviolet rays, and then left for a predetermined time (24 hours or more).
[0150] 24 hours have passed since the coating liquid was impregnated into the acrylic substrate (base material) of the polyester fiber (2), and an organic / inorganic hybrid coating film has been formed (deposited) on the surface of the polyester fiber (2). The organic / inorganic hybrid coating film formed on the surface of the polyester fiber (2) (base material) contains 7% by volume of glass particles, and the average particle diameter D of the glass particles is 50 The aggregate of polyester fibers (1) (substrate) and the gas to be measured were placed in the first sampling bag, and the aggregate of polyester fibers (2) (substrate) and the gas to be measured were placed in the second sampling bag. After leaving them for 2 hours, the gas concentrations in the sampling bags were measured with a detector tube, and the reduction rates were calculated.
[0151] The reduction rate of the gas concentration (ammonia, acetic acid, isovaleric acid, inenal, methyl mercaptan, hydrogen sulfide, indole, pyridine, trimethylamine) after leaving the first sampling bag containing the aggregate of polyester fiber (1) for 2 hours was 0. In contrast, when the gas concentration of the first sampling bag containing the aggregate of polyester fiber (2) was measured after leaving it for 2 hours, the reduction rate of ammonia was 29%, the reduction rate of acetic acid was 64%, the reduction rate of isovaleric acid was 54%, the reduction rate of inenal was 34%, the reduction rate of methyl mercaptan was 25%, the reduction rate of hydrogen sulfide was 30%, the reduction rate of indole was 92%, the reduction rate of pyridine was 9%, and the reduction rate of trimethylamine was 13%. In the case of polyester fiber (2), the concentration of all gases was reduced. As is clear from FIG. 14, it was found that the organic / inorganic hybrid coating film containing the above-mentioned glass particles has an excellent deodorizing effect. [Brief description of the drawings]
[0152] [Figure 1] An enlarged cross-sectional image of an organic / inorganic hybrid coating film formed on the surface of a substrate. [Diagram 2] Cross-sectional diagrams explaining in chronological order the mechanism by which an organic / inorganic hybrid coating film is formed from a coating liquid on the surface of a substrate to which the coating liquid has been applied. [Diagram 3] FIG. 2 is a cross-sectional view showing a schematic example of a state immediately after a coating liquid is applied to a surface of a substrate. [Figure 4] FIG. 2 is a cross-sectional view showing a schematic example of a state after an organic / inorganic hybrid coating film is formed on the surface of a substrate. [Diagram 5] FIG. 4 is a cross-sectional view showing a schematic diagram of another example of a state immediately after the coating liquid is applied to the surface of the substrate. [Figure 6] FIG. 4 is a cross-sectional view showing a schematic example of another example of the state after an organic / inorganic hybrid coating film is formed on the surface of a substrate. [Figure 7] An image showing an example of the structure of an organic / inorganic hybrid coating film. [Figure 8]An image showing an example of the state of metal ions in an organic / inorganic hybrid coating film. [Figure 9] FIG. 1 is a graph showing the relationship between time and antiviral activity value in an organic / inorganic hybrid coating film formed from a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed therein. [Figure 10] A graph showing the change in antiviral activity value over time after a coating liquid containing glass particles mixed with organopolysiloxane (siloxane-based solution) as the main component was applied to the surface of a substrate. [Figure 11] FIG. 1 shows the antibacterial activity value of an organic / inorganic hybrid coating film formed from a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed therein. [Figure 12] 1 is a graph showing the relationship between the glass particle content and antibacterial activity value of an organic / inorganic hybrid coating film. [Figure 13] FIG. 1 shows the mold resistance evaluation of an organic / inorganic hybrid coating film formed from a coating solution containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed in. [Figure 14] FIG. 1 shows an evaluation of the deodorizing performance of an organic / inorganic hybrid coating film formed from a coating liquid containing organopolysiloxane (siloxane-based solution) as the main component and glass particles mixed therein. [Explanation of symbols]
[0153] 10 Organic / inorganic hybrid coating film (coating film) 11 Base material 12 sides (front, back) (contact surfaces) 13 Coating fluid (organic and inorganic hybrid polymers) 14 Glass particles 15 Metal ions 15a Silver ion (Ag + ) 15b Copper ion (Cu 2+ ) 15c Zinc ion (Zn 2+ ) 16 Surface layer 17 Covering layer 18 Back layer 19 Middle Class 20 Anchor section
Claims
1. In coating films containing dispersed glass particles, The coating film is made of silicon oxide (SiO 2 ) is a glass-based coating film based on The glass particles contain silver ions (Ag + ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ) ) ) ) ).
2. The glass particles dispersed and mixed in the coating film are + ) and the copper ion (Cu 2+ ) and the zinc ion (Zn 2+ ) and the silver ion (Ag + ) and the copper ion (Cu 2+ ) and the zinc ion (Zn 2+ 2. The coating film according to claim 1, which is a conductive glass containing at least one of:
3. The glass particles dispersed and mixed in the coating film are + ), the conductive glass containing only copper ions (Cu 2+ ), conductive glass containing only zinc ions (Zn 2+ 2. The coating film according to claim 1, which is a conductive glass containing only .
4. The glass particles dispersed and mixed in the coating film are + ) and the copper ion (Cu 2+ ) and the conductive glass containing only zinc ions (Zn 2+ ) and a conductive glass containing only silver ions (Ag + 4. The coating film according to claim 3, which is a conductive glass containing only .
5. The glass particles are made of vanadium oxide (V 2 O 5 ), tungsten oxide (WO 3 ), molybdenum oxide (MoO 3 At least one of phosphorus oxide (P 2 O 5 4. The coating film according to claim 2 or 3, comprising a glass based on
6. The glass particles are + Vanadium oxide (V 2 O 5 ) -phosphorus oxide (P 2 O 5 6. The coating film according to claim 5, which is a glass of the type SiO2.
7. The coating film according to claim 6 , wherein the glass particles further contain barium oxide (BaO).
8. 8. The coating film according to claim 7, wherein the content of the glass particles dispersed and mixed in the coating film is 0.1% by volume or more and 30% by volume or less.
9. 9. The coating film according to claim 8, wherein the content of the glass particles dispersed and mixed in the coating film is 0.2% by volume or more and 10% by volume or less.
10. The average particle diameter D of the glass particles 50 The coating film according to claim 9, wherein the thickness is 5 μm or less.
11. The average particle diameter D of the glass particles 50 The coating film according to claim 10, wherein the thickness is 3 μm or less.
12. The coating film according to claim 11, in which, after a coating liquid for forming the coating film is coated on a surface of a predetermined substrate, metal ions of the glass particles mixed in the coating liquid diffuse into the inside of the coating film.
13. The coating film according to claim 12, wherein metal ions of the glass particles mixed in the coating liquid diffuse inside the coating film and move to the surface of the coating film.
14. The coating film according to claim 13, wherein the original solution of the coating liquid (the starting material of the coating film) is a siloxane-based solution or a silica sol-based solution, and the glass particles are mixed into the siloxane-based solution or the silica sol-based solution.
15. The coating film according to claim 14, which is a glass-based organic / inorganic hybrid coating film.
Citation Information
Patent Citations
Antibacterial coating composition and its use
JP1995126555A
Antimicrobial coating composition, method for coating the same and product therefrom
JP1996027404A
Antimicrobial coating agent for toilet bowl application and antimicrobial method for toilet bowl
JP2008308437A
Glass with film and film-forming composition
JP2016033109A